Extensive accumulation of misfolded protein aggregates during natural aging and senescence - Cuanalo-Contreras, Karina; Schulz, Jonathan; Mukherjee, Abhisek; Park, Kyung-Won; Armijo, Enrique; Soto, Claudio (Frontiers in Aging Neuroscience, 2023)
Accumulation of misfolded protein aggregates is a hallmark event in many age-related protein misfolding disorders, including some of the most prevalent and insidious neurodegenerative diseases. Misfolded protein aggregates produce progressive cell damage, organ dysfunction and clinical changes, which are common also in natural aging. Thus, we hypothesized that aging is associated to the widespread and progressive misfolding and aggregation of many proteins in various tissues. In this study we analyzed whether proteins misfold, aggregate and accumulate during normal aging in three different biological systems, namely senescent cells, C. elegans and mouse tissues collected at different times from youth to old age. Our results show a significant accumulation of misfolded protein aggregates in aged samples as compared to young materials. Indeed, aged samples has between 1.3- to 2.5-fold (depending on the biological system) higher amount of insoluble proteins that young samples. These insoluble proteins exhibit the typical characteristics of disease-associated aggregates, including insolubility in detergents, protease resistance and staining with amyloid-binding dye as well as accumulation in aggresomes. We identified the main proteins accumulating in the aging brain using proteomic studies. These results show that the aged brain contain large amounts of misfolded and likely non-functional species of many proteins, whose soluble versions participate in cellular pathways that play fundamental roles in preserving basic functions, such as protein quality control, synapsis and metabolism. Our findings reveal a putative role for protein misfolding and aggregation in aging.